2011
DOI: 10.1080/13607863.2010.543663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gerotranscendence support group on gerotranscendence perspective, depression, and life satisfaction of institutionalized elders

Abstract: The findings of this study suggest that after participating in a GT support group, institutionalized elders' GT perspective and life satisfaction were enhanced, and depression reduced. The positive effects demonstrated by this study can be extended and applied to the clinical health promotion of institutionalized elders. Ongoing GT intervention is encouraged to promote mental and spiritual health among institutionalized elders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 18 publications
0
38
1
Order By: Relevance
“…Social and individual relations may refer to increased focus on solitude and pondering as well as some role relinquishment [34]. The theory has been used to better understand the importance of reminiscence in older adulthood [35], spirituality [36] and life satisfaction [37]. Some researchers have been critical of the view that spirituality may change with age.…”
Section: Psychosocial Theoriesmentioning
confidence: 99%
“…Social and individual relations may refer to increased focus on solitude and pondering as well as some role relinquishment [34]. The theory has been used to better understand the importance of reminiscence in older adulthood [35], spirituality [36] and life satisfaction [37]. Some researchers have been critical of the view that spirituality may change with age.…”
Section: Psychosocial Theoriesmentioning
confidence: 99%
“…Although generally true, physical disability represents a source of chronic stress that may influence self‐perceived health and impact spiritual well‐being (Koenig et al., ; Wang & Laffrey, ). In Taiwan, the physical needs of institutionalized elders with disabilities are often met by institutional caregivers (Wang et al., ). With little need to overcome functional decline, spiritual well‐being may not necessarily be affected by self‐perceived health and physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…With the aging of populations and the increasing prevalence of chronic disorders, healthcare systems face challenges in providing high‐quality care for institutionalized older adults. Empirical studies show that older adults living in residential and nursing care settings frequently suffer from functional decline, mental illness, economic losses, and social isolation, all of which make them more vulnerable to loss of personal meaning in life and the will to live (Unterrainer, Lewis, & Fink, ; Wang, Lin, & Hsieh, ). Thus, various researchers have found that increased spiritual well‐being may improve the health status and quality of life of chronically ill older adults (Coleman et al, ; McCauley, Tarpley, Haaz, & Bartlett, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elderly participants showed acceptance of difficulties and yet sensitivity, love for others, and satisfaction with life. A study carried out with institutionalized elderly patients showed that a supportive group reinforces satisfaction with life among participants (24) .…”
Section: Therapeutic Factorsmentioning
confidence: 99%